Teatro com interpretação para Libras: redes e relações discursivas - Fomin, Carolina Fernandes Rodrigues (2023)
This research is theoretically based on the dialogic perspective of Bakhtin’s Circle on language studies, on translation and interpretation of sign language studies (TISLE), and the theatrical studies aimed at the spectator. Its general objective is to analyze discursive interactions between interlocutors of theatrical performances with interpretation into Brazilian Sign Language (Libras) based on the utterances of deaf spectators, sign language interpreters (SLIs), and theater programmers. Our specific objectives are: (i) to observe and describe how the sign language interpretation in the theater has been taking place, including the adaptations that were necessary during the pandemic period; (ii) to analyze dialogical relationships and discourses of different groups: sign language interpreters (SLIs), deaf spectator interlocutors, and theater programmers; (iii) to discuss the implications of these dialogical relationships in the artistic experience of deaf spectators. Based on this objective, this research proposes to answer the following questions: a) how is the deaf public's access to the theater offered? b) How does the deaf public experience the artistic experience of spectacles? c) what are the existing tensions and clashes in the discursive interaction of deaf interlocutors, translators and interpreters, and theater producers? To do so, we undertook qualitative research, whose corpus was made up of group interviews with (a) sign language translators and interpreters; (b) deaf spectators; (c) theater programmers from a cultural institution. The choice and delimitation of our research corpus were motivated by the intention of putting in a dialogical relationship between the discourse about the theater with sign language interpretation from different enunciative perspectives, through interviews. The hypothesis is that despite the institutional discourse about accessibility pointing to the inclusion of deaf people in cultural spaces, there are still many tensions and discursive clashes between interlocutors, theater producers, sign language interpreters, and deaf people; and, regarding the performance of SLIs and the participation of deaf spectators, these tensions directly affect the experience with the aesthetic object